Analysis of Harmful Heavy Metals and Carbonaceous Components in Urban School PM2.5 - Seok Won Kang; Sumin Lee; Jiyou Kwoun; Tae Jung Lee; Young Min Jo (Aerosol and Air Quality Research)
Abstract Harmful heavy metals and carbonaceous substances contained in PM2.5 collected from 53 schools located in large Korean cities were closely analyzed based on the hypothesis that emission sources such as automobiles are coincident. The average concentration of PM2.5 from the analysis of all classrooms was 20.7 µg m−3. Mn was the most prevalent heavy metal with a concentration of 0.018 µg m−3, followed by Pb and Cu. The heavy metals were closely related to elemental carbon (EC) introduced mainly from the outside with a correlation coefficient of 0.556, showing consistent significance. Organic carbon (OC) showed a correlation coefficient of 0.357, which statistically supported the presence of obvious OC sources in the classroom. Overall school classroom contamination levels have been shown to be below national guideline.